2019
DOI: 10.1002/bjs.11239
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of the AVOD randomized trial of antibiotic avoidance in uncomplicated diverticulitis

Abstract: Background: The aim of this study was to assess the long-term results in patients with uncomplicated diverticulitis who had participated in the Antibiotics in Acute Uncomplicated Diverticulitis (AVOD) RCT, which randomized patients with CT-verified left-sided acute uncomplicated diverticulitis to management without or with antibiotics. Methods:The medical records of patients who had participated in the AVOD trial were reviewed for long-term results such as recurrences, complications and surgery. Quality-of-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 17 publications
(20 reference statements)
0
54
0
5
Order By: Relevance
“…In general, the treatment of diverticulitis has shifted towards less aggressive approaches, which might also have beneficial effects on associated costs 31 . The avoidance of antibiotics for uncomplicated diverticulitis has been proven to be safe in both the short and long term [32][33][34][35] . The role of percutaneous drainage for diverticulitis with abscess formation has been debated 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, the treatment of diverticulitis has shifted towards less aggressive approaches, which might also have beneficial effects on associated costs 31 . The avoidance of antibiotics for uncomplicated diverticulitis has been proven to be safe in both the short and long term [32][33][34][35] . The role of percutaneous drainage for diverticulitis with abscess formation has been debated 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is useful for classifying both acute uncomplicated and complicated diverticulitis although there is little validation. Two randomized clinical trials (AVOD [84,85] and DIABOLO [71,86] antibiotic and nonantibiotic treatment in immunocompetent and nonseptic patients with uncomplicated acute diverticulitis. No differences in time to recovery from the initial episode or in hospital stay were seen in the two trials (Data S3; 3.1).…”
Section: Which Ct Classification Is Appropriate?mentioning
confidence: 99%
“…A Twitter poll showed that despite recent studies showing that antibiotics are unnecessary for uncomplicated diverticulitis the majority still prescribe antibiotics in this context.…”
mentioning
confidence: 99%